Avaliação dos efeitos e variáveis do processo de intervenção com mães de crianças com problemas internalizantes - Orti, Natália Pinheiro [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Internalizing problems such as anxiety and depression are related and maintained to different types of variables, including parenting practices. However, rarely parent interventions to present and treat internalizing problems are studied. This research consists of three complementary studies on this topic. A literature review was was conducted, in review was conducted, in which there were identified predictors related to the maintenance and prevention of internalizing problems concerning parenting practices and parents psychopathology. Interventions which included parents in the prevention of internalizing problems were also assessed e discussed. The second study refers to the evaluation of the effects of a semi-structural intervention conducted exclusively with mothers of internalizing children. Three clinical cases were studied from the consent of the participants. The intervention aimed to promote the development of positive parenting practices as indicated by the literature on behavioral problems, but contingently to the dificulties and demands of each case. Different reporting instruments were used at baseline, posttest and follow-up to assess the effects of the intervention procedure. The main results include the remission of internalizing problems to non-clinical level, increased frequency of children's social skills, increased frequency of positive parenting practices and reduced variability of negative parenting practices. The third study aimed to investigate variables in the clinical process that could characterize the cases through the categorization of complaints, developed content and thrapist-client interaction behaviors. The most frequent complaints of mothers were their own negative parenting practices and the contents most often developed in concern to the children were the skillful expression of positive and negative emotions by the mothers. It was found that mothers complained of undiagnosed externalizing problems and...

Problemas internalizantes, como ansiedade e depressão, tem sua origem e manutenção relacionados a diferentes tipos de variáveis, dentre elas as práticas parentais. Entretanto, raramente são pesquisas intervenções parentais para a prevenção e tratamento de problemas internalizantes. A presente pesquisa consiste em três estudos complementares sobre essa temática. Foi feita uma revisão de literatura pela qual foram mapeados preditores relacionados a manutenção e prevenção de problemas internalizantes com relação à variáveis relacionados à saúde mental dos pais e suas práticas parentais, bem como foram avaliadas intervenções que incluíssem os pais na prevenção de problemas internalizantes. O segundo estudo corresponde à avaliação dos efeitos de uma intervenção semi-estruturada conduzida exclusivamente com mães. Três casos clínicos foram conduzidos e analisados como sujeitos únicos, a partir do consentimento das participantes. A intervenção visava promover o desenvolvimento de práticas parentais indicadas como positivas pela literatura sobre problemas de comportamento, mas de modo contingente às dificuldades e demandas de cada caso. Foram usados diferentes instrumentos de relato validados nas avaliações de linha de base, pré-teste e seguimento para avaliação dos efeitos do procedimento. Os principais efeitos da intervenção incluem a remissão de problemas internalizantes, aumento na freqüencia de habilidades sociais infantis, aumento na freqüência de práticas parentais positivas e redução na variabilidade de práticas parentais negativas. O terceiro estudo teve por objetivo investigar variáveis do processo clínico que caracterizam os casos, a partir da categorização de queixas, conteúdo desenvolvido e comportamentos de interação terapeuta-cliente. As queixas mais frequentes foram práticas parentais negativas e os temas mais frequentemente desenvolvidos com relação aos filhos foram...
Keywords: Anxiety; Ansiedade; Depressão mental; Habilidades sociais; Terapia parenteral